Do Bio-Ethanol and Synthetic Ethanol Produced from Air-Captured CO2 Have the Same Degree of “Greenness” and Relevance to “Fossil C”? - Michele Aresta (Molecules, 2022)
This paper discusses the epochal change in the reputation of carbon dioxide, which is now considered as a raw material alternative to fossil C for the synthesis of chemicals, materials and fuels, as opposed to a waste material that must be confined underground. In particular, its use as renewable C is compared to biomass. In this paper, a specific point is discussed: is ethanol (or any fuel) produced via the catalytic conversion of atmospheric CO2 different from the relevant biomass-sourced product(s)? The answer to this question is very important because it ultimately determines whether or not fuels derived from atmospheric CO2 (either e-fuels or solar fuels) have the right to be subsidized in the same way that biofuels are. Conclusions are drawn demonstrating that ethanol derived from atmospheric CO2 deserves the same benefits as bio-ethanol, with the additional advantage that its synthesis can be less pollutant than its production via the fermentation of sugars. The same concept can be applied to any fuel derived from atmospheric CO2.